Influence of supersaturation on the concentration of ice nucleating particles. Issue 1 (1st January 2018) - Belosi, Franco; Piazza, Matteo; Nicosia, Alessia; Santachiara, Gianni
Abstract: There is a consensus on the increase in ice nucleating particles (INP) concentration from subsaturated to supersaturated water conditions typically associated with clouds (1 ÷ 2%). However, it is important to evaluate the INP concentration trend when water supersaturation further increases, as supercooled clouds contain pockets of high water vapor supersaturation. Three laboratory dry-generated aerosols, two biological (microcrystalline and fibrous cellulose) and one mineral (Arizona test dust), and a field aerosol, sampled on filters, were investigated. Atmospheric aerosol (PM1 and PM10 fractions) was sampled at Capo Granitola (CG, coastal site in Sicily) and the National Research Council (CNR) research area in Bologna (urban background site). The dynamic filter processing chamber (DFPC) was used to explore the ice nucleation of the sampled aerosol in the deposition and condensation freezing modes. Experiments were performed from water subsaturated conditions (water saturation ratio S w  = 0.94) to S w  = 1.1, at T  = −22 °C. At CG we considered separately events with a prevalent contribution of marine aerosol, and those showing a contribution of both marine and continental aerosols. An increase in INP concentration, the aerosol activated fraction (AF) and ice nucleation active surface site density ( n s ) from water subsaturated conditions to S w  = 1.02 was measured in both laboratory and field campaigns. This increase is due to the transition from deposition nucleation to condensation freezing. The highest increases in AF and ns from S w  = 1.02 to S w  = 1.1 were obtained for urban and mixed aerosol and the lowest for marine aerosol. Samplings performed in Bologna showed a high increase in the average INP concentration from PM1 to PM10. Our results show the importance of performing measurements of ice nucleation efficiency for continental aerosol even at supersaturation values higher than those typically associated with clouds, and also considering the contribution of coarse aerosol particles.